Pediatric Gaucher Disease Type 3 Presenting with Oculomotor Apraxia: A Case Report - Margherita Di Costanzo; Nicoletta de Paulis; Giuseppe Cannalire; Nicola Morelli; Giacomo Biasucci (MDPI AG, 2024)
We report on a 4-year-old boy affected by Gaucher disease (GD) type 3, who presented with splenomegaly and a history of oculomotor apraxia. GD is a rare lysosomal storage disorder caused by glucocerebrosidase deficiency with multi-organ involvement. Besides common clinical features such as hepatosplenomegaly and skeletal involvement, less frequent neurological symptoms, such as oculomotor apraxia, are indicative of neuronopathic forms of the disease, namely GD type 3, to be confirmed both by enzyme activity and genetic testing. Overall, GD management requires a multidisciplinary approach involving metabolic pediatricians, neurologists, psychologists, and geneticists, and currently relies on early enzyme replacement therapy. Although enzyme replacement therapy has proved to be effective in improving systemic signs and symptoms, it is unable to alleviate neurological complications once these have occurred, as it does not pass across the blood-brain barrier. Neurological improvements may occur through indirect mechanisms. Thus, our case report aims to highlight the importance of considering GD in the differential diagnosis of pediatric patients presenting with splenomegaly associated with neurological manifestations, as early intervention may significantly modify the disease progression and prevent further irreversible complications.